(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the level of knowledge and the demand for using scraping therapy (gua sha) in healthcare-particularly for the treatment of common cold and musculoskeletal pain-among university students and lecturers. Subjects and methods: A cross-sectional descriptive study was conducted using a self-designed questionnaire among 170 students and lecturers from the two universities: Phenikaa University and the Vietnam University of Traditional Medicine and Pharmacy. Results: A total of 165 returned questionnaires were utilized for the analysis; 62.42% of participants had a moderate level of knowledge regarding the traditional scraping therapy (gua sha), while 37.58% had a low level; no participants were recorded as having no knowledge or a high level of knowledge. When experiencing symptoms such as common cold or musculoskeletal pain, 38.18% of participants chose to use gua sha, a higher rate than those who opted for Western medication (33.94%). The frequency of gua sha usage exceeding 10 times was 13.34%, while 15.75% had never used it. The advantages most highly rated included: effectiveness (66.67%), traditional origin (45.45%), suitability (42.42%), and safety (39.39%). The main limitation reported was the risk of incorrect technique (52.73%). Conclusion: Gua sha therapy remains an important practice in the treatment of common cold, musculoskeletal pain, and traditional medicine health care. However, the level of knowledge about this therapy among university lecturers and students remains limited, lacking in-depth professional understanding and predominantly practiced at home without guidance. There is a need to enhance public education and standardize technical guidelines to ensure safety and to promote the role of traditional medicine in modern healthcare.